Karakteristik Isolat Bakteri Penghasil Dekstran dari Batang Tebu (Saccharum officinarum L.) - Sitti Rahbiah Akram; Titi Candra Sunarti; Anja Meryandini (Institut Pertanian Bogor, 2019)
Dextran is a long chain of carbohydrate polymers synthesized by dextransucrase enzyme with sucrose as a substrate. The physical, chemical conditions, temperature, and the concentration of sucrose in the isolate bacterial growth media play an important role in dextransucrase production. This study aims to isolate and characterize the dextransucrase producing bacteria. The bacteria were isolated from sugar cane. TBT 3.2 Isolate which had the highest viscosity (1.48 cP) and crude dextran (7.87 g/L) production was selected. TBT 3.2 Isolate was identified as Paenibacillus polymyxa with 99% similar identity. The Paenibacillus polymyxa TBT 3.2 was characterized based on their ability to produce dextran and cell number. The bacteria had the optimum growth conditions on the media for producing dextran at pH 7, temperature 30°C, and concentration of 20% sucrose. The highest dextransucrase activity and the highest specific activity were obtained after 25 minutes of incubation, with the activities of 29.41 mU/mL and 0.46 U/mg. Based on the results of this study, the Paenibacillus polymyxa TBT 3.2 can be used as a dextran producing bacteria.